Personenverkehr in Europa und Übersee. Wachstumsperspektiven bis 2020. - Rommerskirchen, Stefan; Greinus, Anne; Ickert, Lutz (Deutscher Verkehrs-Verl., 2008)
Im Herbst 2007 hat die ProgTrans AG (Basel) ihren neuen "European Transport Report 2007/2008" vorgelegt - die 4. Ausgabe seit dem Jahr 2000 und die erste Ausgabe, die über den Tellerrand der EU und Europas hinausblickt. Im Beitrag werden die zentralen Basisannahmen und Ergebnisse der Prognosen zur Personenverkehrsentwicklung in den Landverkehrsnetzen sowie zum Personenluftverkehr in Deutschland, West-, Mittel- und Osteuropa sowie China, Japan und den USA vorgestellt. Im Mittelpunkt stehen dabei Entwicklungstrends, Strukturveränderungen und Niveauvergleiche. difu

The 'European Transport Report 2007/2008' compiled by ProgTrans AG (Basel) offers up-to-date analysis-based data up to 2006, plus short and long term forecasts for passenger and freight transport and traffic growth as far ahead as 2020 for a total of thirty-seven European and overseas countries. The report presents all the essential factors forming part of our assumptions, including the forecast results of passenger traffic increases for national land-based transport networks as well as for passenger air transport. Focal points are trends in traffic growth, changes in transport system structures and comparisons of development levels. On a global scale, passenger traffic development in Europe and in selected overseas countries shows significant differences, also with regard to structural modifications. According to our forecasts, the anticipated reduction in passenger traffic demand - occasionally mentioned in the past - in line with individual countries' demographic changes, is deemed unlikely to occur before 2020. In turn, there is evidence to suggest that there will be greatly increased pressure of demand in the field of passenger and freight traffic. difu
Keywords: Verkehr; Personenverkehr; Verkehrsprognose; Bevölkerungsentwicklung; Mobilität; Autoverkehr; Busverkehr; Verkehrsnachfrage; Luftverkehr; Straßenverkehr; Verkehrsnetz; Perspektive; Demographische Entwicklung